Gagasan pemikiran pengaturan hukuman cambuk bagi pelaku nikah sirri dalam rancangan qanun Provinsi Aceh - mistiar, Wolly (Humantech : Jurnal Ilmiah Multidisiplin Indonesia, 2022)
The emergence of the idea of the Caning Punishment Qanun for Siri Marriages in Aceh brought many pros and cons, both by the Indonesian people and religious institutions in the mass media, both print and electronic. to implement Islamic law through Law Number 44 of 1999 concerning the Implementation of Privileges for the Special Region of Aceh. The family law qanun that is made must be able to provide legal protection and certainty to human dignity in a marriage, including the idea of the qanun regarding the Caning Punishment for Siri Marriage Perpetrators in Aceh. This research is important to answer several problems, namely First, how are the criminal sanctions for the perpetrators of unregistered marriages in the perspective of Islamic law. Second, what are the legal consequences that arise from the application of caning as a criminal liability for the perpetrators of unregistered marriages, and Third, why the punishment of canbuk is imposed on the perpetrators. sirrimarriage needs to be implemented in Aceh. Empirical-normative legal research. Empirical legal research, also known as field research, is the collection of research materials or materials that must be sought or searched for by themselves because they are not yet available. The activities carried out can be in the form of making interview guidelines and followed by finding and interviewing informants. In this study, a researcher always bases his thoughts on the rule of law as the main legal material for research. The collected legal materials were analyzed with a qualitative normative juridical method. Where, with this method is expected to obtain a clear picture of the subject matter. In this study, the authors analyze the idea of setting the Caning Punishment for Siri Marriage Perpetrators in the draft qanun for family law in Aceh (response of Indonesian religious institutions and society).